PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Monalisa Ibrahim; Eviyanti Eviyanti (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
This research aims 1). to find out the influence of Organizational Culture on Employee Performance at the Village Office in Timoreng Panua, District of Panca Rijang, Sidenreng Rappang Regency. 2). To find out the Work Discipline on Employee Performance at the Timoreng Panua Village Office, Panca Rijang District, Sidenreng Rappang Regency. 3). To determine the effect of Organizational Culture and Work Discipline on Employee Performance at the Village Office in Timoreng Panua, District of Panca Rijang, Sidenreng Rappang Regency. The sampling technique uses saturated sampling technique with a total sample of 46 people. Data collection techniques using observation, interviews, questionnaires and literature study. Quantitative data analysis techniques used are frequency tabulation analysis and simple regression analysis with the help of the SPSS program.Based on the results of the processing of multiple linear regression analysis using SPSS 16.0 for windows, the influence of Organizational Culture (X.1) on Employee Performance (Y) is calculated t value 0.969 <t table = 1.680 with a significance value of 0.000 <0.05 with a percentage of 54%. Effect of Discipline (X.2) on Employee Performance (Y) is known t count value of 0.420 <t table = 1.680 with a significance value of 0.000 <0.05 with a percentage of 46.3%, and the influence of Organizational Culture (X.1), Discipline (X.2) on Employee Performance (Y) is known t count value of 8.083> t table = 1.680 with a significance value of 0.000 <0.05 with a percentage of 48%, it can be said that the positive hypothesis (Ha) is accepted and the negative hypothesis (Ho) rejected.